Literary reading of the Exodus story - Hughes, Paul Edward (The University of Edinburgh, 1994)
The present work offers an explication of Exodus 1-14 in the Masoretic text from a literary perspective and questions the methodological relationship between Narrative Criticism and traditional Historical Criticism. Chapter One outlines a set of theoretical assumptions upon which the reading of Exodus is based with regard to history, referentiality, the diachronic/synchronic relationship, intentionality and ideology. Along with theory, the method being utilised is discussed, particularly with respect to its role in a pluralistic methodological sphere and also in relation to the stance of the interpreter along emic and etic lines of discussion. Chapter Two interacts with a selection of approaches through which the Exodus story has been read and evaluates their usefulness for Narrative Criticism. Chapters Three to Five contain the Narrative Criticism proper as applied to Exodus 1-14: Chapter Three examines the plot of the entire story in a descriptive manner. After an initial survey and consideration of plot from Aristotle onwards, the plot of Exodus 1-14 is subdivided into four main parts: Section I: Exod 1:1-2:25 (.Introduction), Section II: Exod 3:1-7:7 (Ascent), Section III: Exod 7:8-13:16 (Complication) and Section IV: Exod 13:17-14:31 (Conclusion). Chapter Four deals with the characterisation of the story's Introduction (Section I: Exod 1:1-2:25), focusing initially on the diverse characterisation techniques and character types found within its seven pericopae. Then a major section on etiology opens the methodological dialogue between Narrative Criticism and traditional Historical Criticism (with the issue of etiology—Form Criticism) and intimates a positive interrelationship. Chapter Five offers a close reading of the Prologue and initial Plagues triad (Exod 7:8-8:15) from a narrative-critical perspective, and then continues the literary/historical dialogue concerning method, with the entire Plagues narratives (Section III: Exod 7:8-13:16) as primary data. Whereas the narratological function of these narratives is that they offer links with previous and future story-elements through resonances and foreshadowing, at a historical-compositional level they can be seen to represent two separate tradition-complexes. The thesis locates the method of Narrative Criticism within a context of certain issues that are relevant to literary theory. It samples this method by treating the plot of the whole story, the characterisation of the Introduction and the narratology of the Plagues. Finally, the thesis discusses the relationship between Narrative Criticism and issues (like etiology and the compositional development of the story) long discussed by more historical types of criticism.
A literary reading of the Exodus story